Developing a Sustainable Community Extension Program in Teacher Education Through Longitudinal School-To-School Work Immersion - Bacroya-Magbuo, Jerrylyn; Abairo, Ana Mariel Eve M (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study presents the school-to-school Work Immersion Program of FAITH Colleges, designed for Grade 12 students aspiring to become teachers. Guided by the ADDIE model and aligned with the Philippine Professional Standards for Teachers (PPST), the ten-day program immerses participants in key domains, including pedagogy, learning environment, curriculum, community linkages, and professional growth. Implemented for three years with eleven batches, the program was evaluated through post-tests and focus group discussions. Results consistently showed Very Highly Attained ratings, particularly in orientation to school culture and operations. Across cohorts, no significant differences were found (p = 0.218), confirming program stability. However, ICT integration emerged as a recurring challenge, while Year 2 revealed gaps in content knowledge and classroom management. Qualitative analysis highlighted three themes: experiential learning, supportive mentorship, and teacher identity formation. Moving forward, program refinements will prioritize ICT training and pedagogy while sustaining community partnerships. Overall, the FAITH Colleges Work Immersion Program demonstrates how structured immersion fosters competence, reflection, and professional identity in future teachers.